Datelines of world history - Arnold, Guy.; Trease, Geoffrey, 1909-; Sington, Adrian (New York : Warwick Press, 1983)
Presents a history of the world from 40,000 B.C. to the present.
Includes index.
Keywords: World history -- Juvenile literature